Practitioners, pedagogies and professionalism in English for Academic Purposes (EAP): the development of a contested field - Bell, Douglas E. (2016)
This thesis examines key developments and changes which have taken place within the field of English for Academic Purposes (EAP) from the 1960s until the present day. It critically evaluates the effects that these developments have had on EAP as an academic discipline; on the positioning and status of EAP within the academy; and on the work carried out by EAP practitioners, particularly with regard to conceptualizations of professionalism, and understandings of what constitutes practitioner expertise. Drawing on qualitative data generated from in-depth semi-structured interviews with 15 internationally-recognised scholars from EAP, the study presents a particular history of the different stages and developments which have occurred in EAP, and maps how these have impacted not only upon EAP as a discipline, but also upon the work of its practitioners.